The Model of Coaching Narcotics Prisoners in the Correctional Penitentiary - Sulistya Eviningrum; Vasco Fronzoni (Journal of Human Rights, Culture and Legal System, 2022)
The development of narcotics convicts differs from the development of other criminal convicts. This research uses a normative-juridical approach by reviewing the laws and regulations relevant to the legal issues to be solved and discussing the ideal coaching model for victims of narcotics users in prisons today. From this research, it can be concluded that the coaching model for narcotics abuse victims must be oriented towards healing and recovery, either through medical institutions, hospitals, health centers, or social institutions. Thus giving birth to a model of handling that can be applied to victims of narcotics users.